2018
DOI: 10.14309/crj.2018.67
|View full text |Cite
|
Sign up to set email alerts
|

Osteomyelitis as a Result of Pancreaticojejunostomy Stent Migration after Whipple Procedure

Abstract: Pancreaticoduodenectomy, or Whipple procedure, is a high-risk surgical procedure commonly performed for tumors of the pancreatic head. The pancreatico-enteric anastomosis is an important component of this procedure. The maturation and adequate healing of this anastomotic site is critical to decrease the risk of postoperative pancreatic fistulas. The use of stents can help in the healing of this anastomotic site. We present a patient with pancreatic adenocarcinoma who underwent pancreaticoduodenectomy, and pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Migration of these internal stent has been reported with serious consequences 7,8 . Kadowaki et al 7 reported acute pancreatitis in two patients with stent remaining in pancreatic duct and acute cholangitis in one patient with stent migrated into the bile duct.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Migration of these internal stent has been reported with serious consequences 7,8 . Kadowaki et al 7 reported acute pancreatitis in two patients with stent remaining in pancreatic duct and acute cholangitis in one patient with stent migrated into the bile duct.…”
Section: Discussionmentioning
confidence: 99%
“…Migration of these internal stent has been reported with serious consequences. 7,8 Kadowaki et al 7 reported acute pancreatitis in two patients with stent remaining in pancreatic duct and acute cholangitis in one patient with stent migrated into the bile duct. Munis et al 8 reported a case of osteomyelitis as a complication from an entero-spinal fistula secondary to a migrated stent placed at PJ after partial degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreaticoduodenectomy is a high-risk surgical procedure performed by removing the duodenum, the head of the pancreas, the gallbladder, and the bile duct [9]. A critical part of the procedure is the formation of the pancreatico-enteric anastomosis [10]. Therefore, a stent is usually sited to ensure healing of the anastomosis site and to reduce the risk of formation of a postoperative pancreatic fistula.…”
Section: Discussionmentioning
confidence: 99%
“…Stent migration is a rare complication documented in case series and can result in biliary colic, cholangitis, hepatic abscesses, and even osteomyelitis. 4 7 In this patient, the migrated pancreatic stent lodged within the choledochojejunostomy and served as a nidus for stone formation, causing cholangitis. Performing an endoscopic retrograde cholangiopancreatography in patients with pancreaticoduodenectomy anatomy can be challenging but is usually successful with a pediatric colonoscope, as in our patient, or balloon-assisted enteroscopy.…”
Section: Case Reportmentioning
confidence: 99%